The Analysis of the Usage of Lexical Transformations in the Translation of the Words Expressing the Concept “Hospitality” - Eshkuvatovna, Kholmuradova Leyla; qizi, Mamarizaeva Farangiz Zohidjon; Furkatovna, Sharofova Diyora (European Journal of Life Safety and Stability (2660-9630), 2022)
The topic of this article is the classification of types of transformations in the translation of words expressing hospitality, including some issues of lexical equivalence in Uzbek and English literature. And the subject of this article is the novel “Silence” by the famous writer Said Ahmad and its translation into English. Through studying the types of transformation, it is possible to ensure consistency, which is important in translation. There are three main types of transformation: lexical, grammatical, and lexical-grammatical. It is explained with examples that a translator cannot achieve perfect translation of the concept of hospitality without studying all three types of transformation.